Evolutionary dynamics of R2 retroelement and insertion inheritance in the genome of bisexual and parthenogenetic Bacillus rossius populations (Insecta Phasmida). Issue 6 (19th August 2014) - Bonandin, L.; Scavariello, C.; Luchetti, A.; Mantovani, B.
Abstract Theoretical and empirical studies have shown differential management of transposable elements in organisms with different reproductive strategies. To investigate this issue, we analysed the R2 retroelement structure and variability in parthenogenetic and bisexual populations of Bacillus rossius stick insects, as well as insertions inheritance in the offspring of parthenogenetic isolates and of crosses. The B. rossius genome hosts a functional (R2Brfun) and a degenerate (R2Brdeg) element, their presence correlating with neither reproductive strategies nor population distribution. The median‐joining network method indicated that R2Brfun duplicates through a multiple source model, while R2Brdeg is apparently still duplicating via a master gene model. Offspring analyses showed that unisexual and bisexual offspring have a similar number of R2Br‐occupied sites. Multiple or recent shifts from gonochoric to parthenogenetic reproduction may explain the observed data. Moreover, insertion frequency spectra show that higher‐frequency insertions in unisexual offspring significantly outnumber those in bisexual offspring. This suggests that unisexual offspring eliminate insertions with lower efficiency. A comparison with simulated insertion frequencies shows that inherited insertions in unisexual and bisexual offspring are significantly different from the expectation. On the whole, different mechanisms of R2 elimination in unisexual vs bisexual offspring and a complex interplay between recombination effectiveness, natural selection and time can explain the observed data.